CANTEEN TALKS 3 a.m. Thoughts - Shakina Shahlee; Raihana Ahmad Jalaluddin; Wardah Mohd Zuraimee (Penerbit UTHM, 2026)
Between the din of the canteen and the silence of 3am, there are stories often left untold. This book gathers an assortment of anecdotes born from spontaneous conversations, quiet reflections, and raw emotions experienced by the students from Kolej Matrikulasi Johor (KMJ). Canteen Talks & 3am Thoughts is more than just a book. It’s a space to remember, to reflect and maybe even to heal. These stories resonate with anyone who has ever felt lost, hopeful or human